2020
DOI: 10.1007/s00418-020-01864-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organization and histogenesis of adenosquamous carcinoma of the pancreas: evidence supporting the squamous metaplasia concept

Abstract: Adenosquamous carcinoma of the pancreas (ASCAP) is characterized by conventional pancreatic ductal adenocarcinoma (PDAC) and squamous carcinoma components with at least 30% of the tumour showing squamous differentiation. To get further insight into the histogenesis of these lesions, we analysed the cellular organization of ASCAP compared to PDACs. Using Immunohistochemistry and triple immunofluorescence labelling studies for keratins, p63, p40, MUC1, MUC2, MUC5AC, Ki67, and EGFR we demonstrate that many ASCAPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…To date, the etiology of histogenesis of PASC was still unclear. The hypotheses to explain this phenomenon include the disputable collision tumor hypothesis, malignant squamous metaplasia of the ductal adenocarcinoma, and development from a progenitor cell (31)(32)(33)(34)(35)(36). As a result, the epidemiology and clinical course of PASC remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the etiology of histogenesis of PASC was still unclear. The hypotheses to explain this phenomenon include the disputable collision tumor hypothesis, malignant squamous metaplasia of the ductal adenocarcinoma, and development from a progenitor cell (31)(32)(33)(34)(35)(36). As a result, the epidemiology and clinical course of PASC remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous report (Cancer Genome Atlas Research Network, 2017), some of these molecular classifications overlapped significantly, such as ''ADEX'' (Bailey) and ''exocrine-like'' (Collisson), ''Classical (Collisson)'' and ''pancreatic progenitor'' (Bailey), and ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson) and ''basal-like'' (Moffitt) (p < 0.0001, Fisher's exact test). Notably, five adenosquamous carcinoma samples in our cohort were classified into ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson), or ''basal-like'' (Moffit) groups, in line with the understanding for this histological pancreatic cancer subtype (Boecker et al, 2020;Lenkiewicz et al, 2020;Moffitt et al, 2015). Non-negative matrix factorization (NMF)-based proteogenomics subtyping using multiomics data from all 140 tumors revealed four clusters with significant overlap with RNA subtypes (Figures S7B and S7C; Table S7A).…”
Section: Proteogenomic Subtypes With Strong Prognostic Relevancementioning
confidence: 95%
“…Pancreatic ductal cells can transform to squamous epithelium via metaplasia in conditions such as chronic pancreatitis. Recently, it has been reported that the squamous carcinoma component of pancreatic adenosquamous carcinoma originates from preexisting DAC via transdifferentiation [ 21 ]. Similarly, it is not surprising that ACC can transdifferentiate into DAC because acinar cells originally have the ability to transform into duct-like cells via acinar–ductal metaplasia.…”
Section: Discussionmentioning
confidence: 99%